Perlindungan Hukum Konsumen terhadap Tindakan Kekerasan Debt Collector Pelaku Pinjaman Online - Talitha Danti Elvina; Adi Sulistiyono (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Online loan-based financing services are increasingly attracting public interest because of the simplicity and rapidity of the procedure. However, in practice there are often violations of consumer rights, especially in the collection process by debt collectors who use violence and misuse personal information. This research seeks to assess the legal safeguards provided to consumers who use the Rupiah Plus application against such practices. By using a juridical-normative approach by examining applicable laws, regulations, and relevant case studies, this research reveals that although legal protection exists in a normative sense, its enforcement remains inadequate. Protective measures may be taken both preventively and repressively, while conflict resolution can be approached through judicial proceedings or alternative non-litigation methods.